PENGARUH PROBLEM BASED LEARNING BERBANTU WORDWALL UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SEKOLAH DASAR - Rahayu, Sri; Fatimah, Siti; Setiawan, Awan; Sugiri, Atot (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of the Problem-Based Learning model, supported by the Wordwall application, on improving the mathematical critical thinking skills of elementary school students. Problem-Based Learning is regarded as an innovative learning model that emphasizes real-world problem solving, collaboration, and the development of higher-order thinking skills. The study employed a quasi-experimental design with a quantitative approach, involving 40 second-grade students at SDI Insan Mandiri. Data were collected through tests and documentation, then analyzed using SPSS. Hypothesis testing—conducted on the experimental and control groups using the N-Gain t-test—revealed a significance value (2-tailed) of 0.001 (p < 0.05), indicating that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. Thus, it can be concluded that there is a significant difference in the improvement of mathematical critical thinking skills between students taught using the Wordwall-assisted PBL model and those receiving conventional instruction. This demonstrates that the use of the Wordwall-assisted PBL model influences students' mathematical critical thinking skills.